2011
DOI: 10.1177/1359104511410804
|View full text |Cite
|
Sign up to set email alerts
|

Nigerian secondary school children’s knowledge of and attitudes to mental health and illness

Abstract: Nigerian schoolchildren, as with Nigerian adults and young people in Western countries, show stigma towards mental illness. This may be underpinned by a lack of knowledge regarding mental health problems. Educational interventions need to be appropriate to area, age and gender to effectively improve mental health literacy, which in turn will influence attitudes and social distance. However, the fact that the schoolchildren were optimistic about recovery is a strength that could be built upon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 37 publications
(60 reference statements)
2
46
1
Order By: Relevance
“…Previous work among young people in this environment has shown that stigma is highly prevalent, knowledge about mental illness is poor, and attitudes towards people with mental illness are largely negative (Ronzoni et al 2010, Dogra et al 2012. As a follow-up, this study reports the impact of a school-based mental health awareness programme aimed at increasing mental health literacy among young people and reducing negative views about persons with mental illness.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Previous work among young people in this environment has shown that stigma is highly prevalent, knowledge about mental illness is poor, and attitudes towards people with mental illness are largely negative (Ronzoni et al 2010, Dogra et al 2012. As a follow-up, this study reports the impact of a school-based mental health awareness programme aimed at increasing mental health literacy among young people and reducing negative views about persons with mental illness.…”
Section: Introductionmentioning
confidence: 83%
“…Though stigmatising attitudes towards people suffering from mental illness have been well described in the Nigerian context (Adewuya and Makanjuola 2005, Gureje et al 2005, Ronzoni et al 2010, Dogra et al 2012), very few programmes have aimed at reducing stigma, especially among young people in this part of the world. Previous work among young people in this environment has shown that stigma is highly prevalent, knowledge about mental illness is poor, and attitudes towards people with mental illness are largely negative (Ronzoni et al 2010, Dogra et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…One way of approaching this is through providing tailored psycho-education in schools. Research has shown that there are gaps in young people's knowledge of mental health (Dogra et al, 2012a). However Svirydzenka et al (2014) found that students were able to use a broad range of themes when discussing mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Research has indicated that many young people worldwide are not well informed about mental health (Dogra et al, 2012a;Pinfold et al, 2003;Ronzoni et al, 2010;Rose et al, 2007;Sessa, 2005;Sheffield et al, 2004;Stengard and Appelqvist-Schmidlechner, 2010). As young people spend a significant amount of their lives in school, school-based interventions are therefore an important factor to consider regarding the promotion of mental health.…”
Section: Introductionmentioning
confidence: 99%
“…The importance and challenge of addressing MHL in young people globally is well-documented [2,[25][26][27][28][29]. A recent systematic review of community MHL in Sub-Saharan Africa reported that the predominant perspective of the cause of mental illness is that it is the result of ultra-human or supernatural forces [30].…”
Section: Introductionmentioning
confidence: 99%